Perinatal outcomes after intrauterine growth restriction and umbilical artery Doppler pulsatility index of less than the fifth percentile. (4th March 2021) - Lewkowitz, Adam K.; Tuuli, Methodius G.; Cahill, Alison G.; Macones, George A.; Dicke, Jeffrey M.
Abstract: Objective: To analyze perinatal morbidity and stillbirth after intrauterine growth restriction (IUGR) with an umbilical artery Doppler pulsatility index (UA PI) less than the fifth centile. Study design: This retrospective cohort study included nonanomalous singleton, IUGR pregnancies receiving UA PI testing at a tertiary-care prenatal diagnostic center. Women with persistently elevated UA PI, absent or reversed end-diastolic flow on UA PI, or who had only one UA PI result were excluded. Low UA PI was defined as having ≥1 UA PI <5%. Women with low UA PI were matched by gestational age at IUGR diagnosis in a random 1 case: 4 control computer-generated algorithm to those with normal UA PI (≤95% and ≥5%). The primary outcome was composite neonatal morbidity and mortality (stillbirth, mechanical ventilation, sepsis, intraventricular hemorrhage, and necrotizing enterocolitis). Secondary outcomes included 5-minute Apgar, umbilical artery pH, delivery type, and interval from IUGR diagnosis to delivery. We compared outcomes after low UA PI to those after normal UA PI with multivariable logistic regression, adjusting for gestational age at delivery, betamethasone use, infant gender, and maternal factors. Results: Of the 1893 IUGR pregnancies, 25 (1.3%) had low UA PI <5% and were randomly matched via computer algorithm to 100 controls. There were no stillbirths in either group; the odds of composite neonatal morbidity was similar among IUGR pregnancies with UA PI <5% versus normal (adjusted odds ratio 0.89 (95% confidence interval 0.27–2.75)). There was no difference in 5-minute Apgars, umbilical artery pH, rate of cesarean delivery for fetal distress, or interval from IUGR diagnosis to delivery between the two groups. Conclusion: Among IUGR pregnancies, UA PI <5% is uncommon and not associated with improved neonatal outcomes compared to normal UA PI. These findings suggest low UA PI can continue to be managed as normal UA PI.